고추 유전자원의 카로티노이드 조성 및 ASTA color 지수 분석 - 윤장언(Jang-Eon Yoon); 김정봉(Jung-Bong Kim); 김헌웅(Heon-Woong Kim); 장길수(Kil-Soo Jang); 고호철(Ho-Cheol Ko); 장환희Hwan-Hee Jang; 이성현Sung-hyen Lee; 황유진(Yu-Jin Hwang) (Korean journal of breeding, 2015)
영양고추시험장에서 분양 받은 고추 유전자원 523종에 대한 카로티노이드의 정성 및 정량 분석과 ASTA color 지수를 분석하였다. 개별 카로티노이드는 capsanthin, lutein, zeaxanthin, β-cryptoxanthin, α-carotene, β-carotene 등으로 동정하였다. 총 카로티노이드 함량은 0.5-84.8 mg/100g DW으로 나타났으며 ASTA color 지수는 0.7-233.1로 나타났다. 개별 카로티노이드의 평균갑과 총 카로티노이드 함량에 대한 비율은 β-carotene 5.0 mg/100g DW (24.8%) > capsanthin 5.0 mg/100g DW (24.7%) > zeaxanthin 4.1 mg/100g DW (20.4%) > β-cryptoxanthin 3.0 mg/100g DW (14.8%) > lutein 2.7 mg/100g DW (13.3%) > α-carotene 0.4 mg/100g DW (2.0%) 순으로 분석되었다. 카로티노이드 중 capsanthin의 함량이 ASTA color 지수와 높은 상관관계를 보였으며 (R2 = 0.723) capsanthin이 23.2 mg/100g DW으로 고함유된 자원 IT223599를 선발하였다. 또한 카로티노이드 크로마토그램의 패턴에 따라 고추유전자원을 7가지 그룹으로 구분하였으며 이는 고 색소 함유 품종 육종 등 다양한 산업 소재로 활용 될 수 있다. Peppers (Capsicum annum L.) were harvested from 523 different genotypes cultivated at the Pepper Experiment Station in Gyeongsangbuk-do Agricultural Technology Administration of Yeongyang in the northeast region of Korea. The investigation of pepper with high carotenoids contents was quantitatively and qualitatively analysed by HPLC. The individual carotenoids were separated as capsanthin, lutein, zeaxanthin, β-cryptoxanthin, α-carotene and β-carotene by reverse-phase HPLC and identified with their external standards. The levels of total carotenoids and ASTA color values in 523 peppers were 0.5-84.8 mg/100g of dry weight (DW) and 0.7-233.1, respectively. Individual carotenoid content and percentage of total carotenoid content were shown as follows: β-carotene (24.8%) (average 5.0 mg/100g DW) > capsanthin (24.7%) (average 5.0 mg/100g DW) > zeaxanthin (20.4%) (average 4.1 mg/100g DW) > β-cryptoxanthin (14.8%) (average 3.0 mg/100g DW) > lutein (13.3%) (average 2.7 mg/100g DW) > α-carotene (2.0%) (average 0.4 mg/100g DW). As a result of plotting by using SIMCA, ASTA color values showed that the cluster is created.